Sacred stories, spiritual tribes : finding religion in everyday life - Ammerman, Nancy Tatom, 1950- (New York : Oxford University Press, 2013)
Nancy Tatom Ammerman examines the stories Americans tell of their everyday lives, from dinner table to office and shopping mall to doctor's office, about the things that matter most to them and the routines they take for granted, and the times and places where the everyday and ordinary meet the spiritual.
In search of religion in everyday life -- "Spirituality" and "religion": what are we talking about? -- Spiritual practices in everyday life -- Religious communities and spiritual conversations -- Everyday life at home -- Nine to five: spiritual presence at work -- Everyday public life: circles of spiritual presence and absence -- Bodies and spirits: health, illness and mortality -- Spiritual tribes: toward a sociology of religion in everyday life -- Participants and their religious communities -- Coding and analyzing stories -- Research protocols.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Spirituality -- United States; Religion; United States -- Religious life and customs; Religion; Spiritualité -- États-Unis.; Religion; religion (discipline); SOCIAL SCIENCE -- Sociology of Religion; Religion; Spirituality; United States; Spirituality -- Religion. -- United States